Gliomatosis Cerebri: a rare Malignant Tumour of Brain - V, Lokesh; T, Naveen; Khaleel, I.; P, Siddanna; Pawar, Y.; ., Deepika; R, Pramod K P (Asian Journal of Medical Research, 2013)
Gliomatosis cerebri is a rare form of brain glioma with incidence of less than 1% of total brain tumors .Gliomatosis cerebri is an infiltrative astrocytic tumor which has acquired the status of a distinct clinical, radiological and pathological entity where the diffuse neoplasm involves two or more lobes of cerebrum.